Structural Characteristics, Mechanization Applications, Problems and Solution Suggestions of Poultry Houses of Broiler Chickens in Bolu Central District - Kerem Aytimur; Ebubekir Altuntaş; Sedat Karaman (Turkish Journal of Agriculture: Food Science and Technology)
In this study, structural characteristics, mechanization applications, problems and solution suggestions of poultry houses of broiler chickens in Bolu central district were investigated. The surveys were conducted in a total of 200 broilers in 8 villages (Oğulduruk, Taps, Değirmenbeli, Çivril, Banaz, Yakuplar, Vakıfgeçitveren and Çaygökpınar) where the broiler production of the central district of Bolu was intensively produced. The field work for the surveys was conducted in February-April 2018. In the broiler houses surveyed in the central district of Bolu, it was determined that the capacity was generally in the range of 5.000 ≤ Capacity < 20.000 (74%), and nearly all of the houses (96.5%) were in the east-west direction. It was determined that the concrete materials are used in the foundations of all the houses examined, and %79 Sandwich panel on the walls and 86.5% of the poultry houses are used mechanical ventilated, in 70% of the poultry houses have 9 and more fans for ventilation, and in all of the poultry house are used luminaires for illumination.It was determined that 91.5% of the poultry houses had a tractor, 96% of the poultry houses had full automatic watering, and nipple drinker with lifting system was used and 87.5% of the poultry houses had honeycomb (Ped) application. It was determined that the number of animals placed in 1 m² was 16-18 (42.5%). It was determined that 15.5% of the problem, 13% of deficiency of information with the broiler houses, 20% of credit and debt problems. Then, there should be a solution to the problem of disease among the producer problems in the enterprises examined and the credit facilities should be improved. In addition, manufacturers need to be informed according to new technological developments in information deficiencies.